Role of Society Sada Ahmo (PESADA) In Increasing Consciousness Politics Women - Reni Andriani (Institute of Computer Science (IOCS), 2019)
More than half the Indonesia's population is women with the level of participation in the elections which quite high, however very unfortunate participation of which done of women still are passive or without consciousness full. This case not apart rather than political consciousness of women who can said to be low let alone in level regions/village because of the limited opportunity and access who obtained by women. Political rights of women are also not fully understood as individual rights, but very patriarchal or based on power relations around women, for example, a wife who followed her husband's political choice. And this is also caused by the functioning of political parties in providing political education to the public, it needed an alternative to other agencies in conducting political education and one of these institutions is Non-Governmental Organization (NGO) or commonly referred to as non-governmental organizations (NGO). Therefore, in this study I will try to elaborate or describe the role of NGOs/NGO Sada Ahmo Society (Pesada) in its efforts to increase women's political consciousness. Theory is used to analyze the study was the theory of the role, NGOs/NGO, the theory of political participation through new social movements, political consciousness theory, gender theory and feminist theory to determine or as an approach to understanding women's movement. Pesada have a role in increasing women's political awareness with the political education program Education / Gender Awareness, Discussion Regarding the Issue of Women, Introduction to Law No.7/1984, Introduction to Government Systems and Political Law, Education Introduction to Gender Based Violence, Discussion on Regional Autonomy Law, as well as Field practices such as hearings, action and dialogue.